Synthesis of a novel photochemical and thermoresponsive diblock biomaterial with end-functionalized zinc porphyrin - Qiu, Nannan; Pan, Xinyuan; Hu, Ruizhang; Hui, Zhenzhen (Frontiers in Bioengineering and Biotechnology, 2023)
Porphyrin compound-based photochemical molecules and biomaterials have been synthesized for photosensitivity and bioimaging experiments. However, most porphyrin photosensitizers have limited application in biological environments owing to severe aggregation in aqueous solutions. In the present study, we prepared amphipathic and photosensitive copolymers using zinc porphyrin via consecutive atom transfer-free radical polymerizations (ATRPs) comprising photoresponsive and thermosensitive chain segments. Furthermore, we evaluated the photocatalytic activity of the copolymer for methylene blue (MB) in water. Methods: First, we synthesized a photoresponsive ain segment of poly (6-[4-(4-methoxyphenylazo)phenoxy]hexyl methacrylate) (ZnPor-PAzo); then, ZnPor-PAzo was used as a macroinitiator and was polymerized with N-isopropylacrylamide (NIPAM) via ATRPs to obtain a novel photochemical and thermoresponsive diblock biomaterial with end-functionalized zinc porphyrin [(ZnPor-PAzo)–PNIPAMs]. Results: The polydispersity index (Mw/Mn) of (ZnPor-PAzo)–PNIPAMs was 1.19–1.32. Furthermore, its photoresponsive and thermosensitive characteristics were comprehensively studied. Discussion: The end-functionalized diblock copolymer (ZnPor-PAzo)–PNIPAM exhibits obvious fluorescence and efficient photocatalytic activity for aqueous MB under visible light.